(untitled) (Ágora Journal, 2025)
This article’s goal is to address the culture of violence that existed in the society of the 1800s. The text draws a cross-checking through guardianship and apprenticeship lawsuits from the end of the 19th century — kept in the Arquivo Nacional, in the archival fond Juízo dos Órfãos e Ausentes, with newspapers and literary works. Wonders with the limits of the legal interventions before these "educational" acts in their legal guardians’ homes. Between 1880 and 1908, Rio de Janeiro went through the peak and decline of these claims, in which the claimants promised to provide education to the impoverished minors, but inserted them in violent work relationships guided by the slavery mindset. We will use the Pierre Bourdieu’s theoretical suggestions, the concept of culture of violence from Ivan Vellasco, besides Carlo Ginzburg’s evidential paradigm.